2022
DOI: 10.3949/ccjm.89a.21126
|View full text |Cite
|
Sign up to set email alerts
|

Common skin signs of COVID-19 in adults: An update

Abstract: A s experience with caring for patients with COVID-19 has accumulated since the onset of the pandemic, so has our understanding of its associated cutaneous manifestations and their clinical implications.It is benefi cial to watch for cutaneous manifestations of COVID-19, both in and out of the hospital. For example, a study of more than 330,000 community-based patients in the United Kingdom 1 found that patientreported skin rash was associated with positive COVID-19 testing and was more predictive than fever. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…In adults, it has been shown that these COVID‐associated vaso‐occlusive lesions occur predominantly in hospitalized patients 12,33 . The presence of a COVID‐associated rash in an adult suggested that our patient was at a higher risk for severe COVID‐19 illness.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In adults, it has been shown that these COVID‐associated vaso‐occlusive lesions occur predominantly in hospitalized patients 12,33 . The presence of a COVID‐associated rash in an adult suggested that our patient was at a higher risk for severe COVID‐19 illness.…”
Section: Discussionmentioning
confidence: 82%
“…[29][30][31][32] In adults, it has been shown that these COVIDassociated vaso-occlusive lesions occur predominantly in hospitalized patients. 12,33 The presence of a COVIDassociated rash in an adult suggested that our patient was at a higher risk for severe COVID-19 illness. Her previous immunization may have contributed to the hyperimmune and hyperthrombotic state that manifested with a purpuric rash that required immunomodulation with high dose corticosteroids, monoclonal antibody treatment, and specific antiviral therapy.…”
Section: F I G U R Ementioning
confidence: 88%
“…degeneration [11]. Although diffuse vesicular eruptions, with lesions developing simultaneously on the trunk and spreading distally with possible involvement of the palms and soles have been reported, localized forms with scattered lesions are the most frequent presentations [1,4,12]. Trunk is the most common affected area in these subtypes, yet extremities involvement is not uncommon [3].…”
Section: Vesicular Rashmentioning
confidence: 99%
“…Another nationwide study in Spain found that chilblain-like lesions were associated with less severe COVID-19 cases whereas livedoid and/or necrotic lesions were associated to more severe ones [ 130 ]. Clinical reports have accumulated and it is now admitted that the five most common cutaneous abnormalities that are associated with COVID-19 are morbilliform rash, urticaria, vesicles, pseudo-chilblains and vaso-occlusive lesions [ 131 ]. Some of these symptoms such as skin rash are associated with positive COVID-19 swab testing and a UK study of 330,000 patients found that it was more predictive of infection than fever [ 132 ].…”
Section: Skin As An Alternative Entry Route For Sars-cov-2 Virusmentioning
confidence: 99%